2018
DOI: 10.2478/rela-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Cross-Linguistic Differences and Context in L2 Idiom Comprehension

Abstract: The present study investigates to what extent the effect of cross-linguistic differences on L2 idiom comprehension is modulated by the presence of a context. Sixty students of German as a foreign language (L1 French) completed a comprehension test consisting of metaphorical idioms in the L2 that differed from their L1 equivalents conceptually and formally and were presented with or without context. The results show that an increasing degree of conceptual and formal distance as well as the absence of context ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…As expected, the stay-abroad experience was associated with a better performance on the comprehension test but did not seem to correlate with the presence of context. This substantially adds to empirical evidence from previous studies, which found stay-abroad experience to be a powerful predictor of L2 metaphor comprehension (Suñer, 2018;De Cock & Suñer, 2018), and more generally to research into lexis development in study abroad language learning contexts (McManus, 2023). Stay-abroad experiences are considered to provide learners with valuable opportunities for communication practice in a wide range of formal and informal settings and thus increased exposure to registers that are rarely covered in textbooks, as is the case for linguistic taboo (Berdún Villamonte, 2021).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As expected, the stay-abroad experience was associated with a better performance on the comprehension test but did not seem to correlate with the presence of context. This substantially adds to empirical evidence from previous studies, which found stay-abroad experience to be a powerful predictor of L2 metaphor comprehension (Suñer, 2018;De Cock & Suñer, 2018), and more generally to research into lexis development in study abroad language learning contexts (McManus, 2023). Stay-abroad experiences are considered to provide learners with valuable opportunities for communication practice in a wide range of formal and informal settings and thus increased exposure to registers that are rarely covered in textbooks, as is the case for linguistic taboo (Berdún Villamonte, 2021).…”
Section: Discussionsupporting
confidence: 67%
“…These findings contrast with other studies that focused on the interplay between stay-abroad experience and other item-based factors such as the frequency and the conceptual and formal distance between L2 metaphorical expressions and their L1 equivalents. For example, Suñer (2018) found out that L2 idiom comprehension was positively correlated with the general proficiency level of learners, rather than with stay-abroad experience (see also Galantomos, 2018). A follow-up study by Suñer (2019) showed that participants with a stay-abroad experience neither outperformed those without such an experience nor benefited from frequency effects and the presence of context.…”
Section: Understanding Metaphorical Expressions In the L2mentioning
confidence: 99%
See 1 more Smart Citation
“…Translators must decide whether to preserve the element of "force and levity" of figurative language (Miller and Monti, 2014: ix) and may be constrained by what is idiomatic in the target language. Although this perception as problem is now less widely held (Miller and Monti, 2014;Schäffner, 2017), process-oriented research provides evidence for increased cognitive load when translating linguistic metaphors, both in translation studies (Tirkkonen-Condit, 2002;Sjørup, 2011) and in SLA (De Cock and Suñer, 2018;Suñer, 2018).…”
Section: Morphosyntactic and Conceptual-semantic Aspects Of Translationmentioning
confidence: 99%